ETV6–NTRK3 in congenital mesoblastic nephroma: A report of the SIOP/GPOH nephroblastoma study. Issue 4 (29th December 2017) - Vokuhl, Christian; Nourkami‐Tutdibi, Nasenien; Furtwängler, Rhoikos; Gessler, Manfred; Graf, Norbert; Leuschner, Ivo
Abstract: Background: Congenital mesoblastic nephroma (MN) is a rare pediatric renal tumor representing approximately 5% of all pediatric renal tumors. Three different types of MN are distinguished histologically: classical, cellular, and mixed. A frequent genetic alteration is the translocation t(12;15) resulting in a fusion of the ETV6 gene on 12p13 and the NTRK3 gene on 15p15 that occurs almost exclusively in cellular MN. The aim of this study was to determine translocation status of a large cohort of MN with respect to tumor subtype and outcome. Procedure: In total, clinical data from 111 patients were available. Sixty‐seven tumors were classical MN (51%), 29 cellular MN (31%), and 15 were mixed MN (18%). From these 111 cases, 79 were analyzed by FISH and RT‐PCR. Results: All classical and mixed MN were translocation negative. Seventeen out of 29 (58%) cellular MN harbored the ETV6 – NTRK3 translocation. Five‐year relapse‐free survival (RFS) and overall survival (OS) were 93.2% and 96.8% for the complete cohort. All seven relapses occurred in translocation negative tumors. Five‐year RFS was significantly inferior for cellular and mixed MN compared to classic MN (89%, 80%, and 98%), whereas 5‐year OS was similar (93%, 96%, and 98%). Within the group of cellular MN, patients having translocation‐positive tumors had a significantly superior RFS (5‐year RFS: 100% vs. 73%). Conclusion: The majority of cellular MNs harbor the ETV6 –NTKR3 gene fusion, whereas all classic‐ and mixed‐type MNs were translocation negative. Within the cellular subgroup, patients having translocation‐positive tumors had a significantly superior RFS.